ΕΥΡΙΠΙΔΗΣ ΓΑΡΑΝΤΟΥΔΗΣ, Το ποίημα «Όταν οι ευκάλυπτοι θροΐζουν στις αλλέες» ως λανθάνων άξονας της ποιητικής μυθολογίας του Εμπειρίκου - Γαραντούδης, Ευριπίδης (Σύγκριση/Comparaison/Comparison, 2022)
The poem "When the eucalyptus trees rustle on the alleys" as a latent axis of the poetic mythology of Embiricos The well-known prose poem by Andreas Embirikos, "When the eucalyptus trees rustle in the alleys" (written on 9 December 1964 and published in the collection Octana in 1980), entirely referring to K.G. Karyotakis, is examined as an emblematic landmark in the formation of Embirikos' personal poetic mythology. The main converging views of interpretation of the poem are summarized first, based on the main studies that refer to it. Then, the pragmatic terms of the poem are traced, in other words, the context of what and how, from a purely synchronic point of view, that of 1964, Embirikos knew about Karyotakis' life, his poetry and its critical reception is explored.